Taking Race Live: Exploring experiences of race through interdisciplinary collaboration in higher education (UCL Press, 2019)
In this article we discuss an interdisciplinary and collaborative four-year project, Taking Race Live, that explored lived experiences of race among students enrolled at an ethnically diverse university in England. Utilizing qualitative methods to evaluate the project each year, we draw on students' voices to address their experiences of race, partnering with interdisciplinary peers and learning about each other. Framing the discussion are the concepts of 'liveness' and 'public sociology' proposed by sociologists to bring sociological knowledge alive. Attention is given to how this was done through engaging with the arts and embodied practices found within drama, dance and music.